Financial Inclusion & Implementation of Jan Dhan Yojna – Information Technology as Enabler - Singh, Dr. Alka (International Journal of Scientific Research and Management (IJSRM), 2017)
With the announcement of Pradhan Mantri Jan Dhan Yojna (PMJDY) on 28 August 2014, the current government has once again attempted to implement Financial Inclusion in the country. This scheme is based on “Sab ka sath sab ka vikas” i.e. inclusive growth. It has far reaching impact on the socio-economic lives of people, as it ensures that everyone in the society gets access to social, economic and political opportunities without any discrimination. This facet is strongly linked with the concept of inclusive growth. Technology can play an important role in not only reducing operating cost of providing banking services, particularly in the rural and unbanked areas but also increasing the reach of the financial sector to the remotest areas. There are technologies that could drive the growth in financial inclusion and with further development and innovation in Information Technology it is succeeding in its desired objective.